A vacuum gauge based on an ultracold gas. (June 2017) - Makhalov, V.B.; Turlapov, A.V.
Abstract: We report the design and application of a primary vacuum gauge based on an ultracold gas of atoms in an optical dipole trap. The pressure is calculated from the confinement time for atoms in the trap. The relationship between pressure and confinement time is established from the first principles owing to elimination of all channels introducing losses, except for knocking out an atom from the trap due to collisions with a residual gas particle. The method requires the knowledge of the gas chemical composition in the vacuum chamber, and, in the absence of this information, the systematic error is less than that of the ionisation sensor.